(3fjd Gdefi ef eSCdI ESJMbGb GdeTJQi HYO GdHfGs - (3eMeO Hf HjQe GdKGfjs
(3ChdgG (B:s
(3HYO GdKfGA Ydi ef dg ESJMbGb GdKfGA Yde Cf GdeTJQi EPG CfTC ajeG ETJQGg s
(3BNQgG (B:s
(3eY YOe GdVQQ Ydi GdbOje ai GdQaY hgh eJMbb gfG hdjcf gPG efJgi GdQSGdI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs